Personality dysfunction in opiate addicts on opioid substitution treatment and the risk of HCV infection - Skočibušić, Siniša; Zivlak-Radulović, Nera; Hasanović, Mevludin; Awad, Hassan; Karan-Križanac, Dragana; Mehić-Basara, Nermana; Rukavina, Tomislav (Frontiers in Public Health, 2022)
Background Impulsivity, affective instability, and neglect of oneself and other people's safety as symptoms of personality dysfunction are associated with risky behaviors regarding the transmission of infectious diseases either sexually or by intravenous drug abuse. Objective The aim of this study was to analyze the association between hepatitis C virus (HCV) infection and personality dysfunction in opiate addicts on opioid substitution treatment. Methods This was a cross-sectional, observational investigation of patients over 18 years of age who were actively participating in opioid substitution treatment at five centers in Bosnia and Herzegovina. The occurrence of HCV infection was the primary study outcome, and personality functioning, the main independent variable, was assessed using the Severity Indices of Personality Problems (SIPP−118) questionnaire. The association between scores of personality functioning domains items and HCV infection status was determined by binary logistic regression analysis. Results Patients on opioid substitution therapy with HCV infection more frequently had personality disorders (OR 2.168, 95% CI 1.161–4.05) and were treated longer than patients without HCV infection (OR 1.076, 95% CI 1.015–1.14). HCV infection was associated with lower self-respect (OR 0.946, 95% CI 0.906–0.988), decreased capacity to have enduring relationships with other people (OR 0.878, 95% CI 0.797–0.966), and lower capability to cooperate with others (OR 0.933, 95%CI 0.888–0.98). On the other hand, except for self-respect, other elements of the Identity Integration domain (enjoyment, purposefulness, stable self-image, and self-reflexive functioning), when more functional, increased the risk of HCV infection. Conclusions Our study demonstrates that opiate addicts on opioid substitution treatment have a higher risk of HCV infection if their personality is dysfunctional, especially in the aspects of self-respect, enduring relationships, and cooperativity. The risk is even higher in addicts who have an established diagnosis of any kind of personality disorder.